Are doses of lamotrigine or levetiracetam adjusted during pregnancy?. Issue 1 (27th November 2017) - Richards, Noni; Reith, David; Stitely, Michael; Smith, Alesha
Summary: Subtherapeutic levels of lamotrigine and levetiracetam are more likely to occur during pregnancy owing to the effect of pregnancy on their pharmacokinetics. This can lead to suboptimal control of epilepsy, and guidelines recommend proactive dose adjustment in the second and third trimesters alongside therapeutic drug monitoring (TDM). This retrospective cohort study using administrative databases aimed to investigate whether prescribers adjust the dose of lamotrigine or levetiracetam during and after pregnancy and whether TDM is used to manage dose adjustment. In 460 individual pregnancies, 232 women (61.4%) had their lamotrigine dose increased in the second and third trimesters and 44 women (53.7%) had their levetiracetam dose increased. Only 57 women (12.4%) had any TDM. The dose was not always decreased postpartum, and 157 women (56.9% of those who had escalated doses during pregnancy) had dose reduced following birth. Between 2012 and 2015, 29 women had an epilepsy‐coded hospital discharge during pregnancy and were more likely to have had their dose of lamotrigine or levetiracetam increased. Overall, doses of lamotrigine and levetiracetam were not increased during pregnancy in 40% of the study population, dose changes were not often guided by TDM, and doses were not always reduced postpartum.